Globalization's Influence on Cultural Hybridity and Identity Formation - Aanayo, Chyjindum; Rukayat, Salamatu; Safiya, Hadiza (Journal Social Humanity Perspective, 2023)
This examine delves into the problematic dynamics of globalization's impact on cultural hybridity and identification formation, drawing upon theoretical frameworks which include Bhabha's Third Space, Hall's Encoding/Decoding, and Appadurai's Scapes. Regional analyses of Asia and Africa illuminate numerous responses to globalization, from the variation of Western impacts in Asia to put up-colonial identification struggles in Africa. The Asian diaspora communities exemplify transnational identification negotiations. Across areas, the anxiety among preserving cultural authenticity and assimilating global affects emerges as a important theme. This look at emphasizes the want for a nuanced understanding of identity inside the globalized international, highlighting the numerous and evolving nature of identity formation. The conclusion underscores the significance of cultivating culturally sustainable globalization for fostering inclusivity and understanding in our interconnected global.